Islamist Biographies: Religious Experiences of South African Muslim Activists - Ahjum, Gadija (Department of Religious Studies, 2017)
This thesis explores the biographies of Muslim activists who were involved in the South African Islamist movement from the 1970s, 1980s and 1990s - tracking their trajectories up till the present. These Islamist biographies can be likened to journeys which include moments of fulfilment, doubt, ambivalence and a grappling to make sense of the self and society. A close examination of Islamist journeys reveal accounts of conversion, a deep commitment to religion and the reconstruction of both public and private identities. Conversion signalled both an arrival – at a new meaning system – and a departure – on a journey informed by this new meaning system. For Islamists, their renewed understanding of religion provided purpose, perseverance and direction. They turned to Islamism to reconstruct their public identities by becoming part of a chosen collective. Simultaneously, they also used religious ideology to reconstruct their identities within the private sphere. This study places emphasis on the everyday lives of Islamists. By suggesting that South African Islamism can best be viewed as the sum of a multitude of journeys of everyday political Islam, this study recognizes that such a life is located within a particular idealized world-view. However, interrogating this life trajectory necessitates an in-depth approach which takes heed of Islamists’ perfectionist ideals while remaining cognizant of personal realities. In doing so, this study reveals not only their firm resolve to be ‘good’ Islamists, but also their aspirations to be ‘good’ women within their personal domains. I thus contend that, included in an investigation on Islamist journeys, should be the ambiguities and personal challenges they encountered in private spaces. This study aligns itself with others who have challenged notions of a monolithic Islamism; rather Islamism has proven itself to continuously transform – even within local contexts like South Africa. Moreover, this thesis addresses a lacuna in scholarship on Islamism and highlights key perceptions that Islamists have about themselves, an idealized worldview and the challenges in everyday life. In this way, this study offers an alternate line of enquiry into religious activism as a lived experience. Doing so leads to a better understanding of not just individuals’ ideals and objectives, but also the everyday consequences this had.